Alcohol Availability, Prenatal Conditions, and Long-Term Economic Outcomes - Nilsson, J. Peter (Journal of Political Economy, 2017)
This study examines how a policy that sharply increased alcohol availability during 8.5 months affected the labor productivity of those exposed to it in utero. Compared to the surrounding cohorts, the prenatally exposed children have substantially worse labor market and educational outcomes and lower cognitive and noncognitive ability. Effects on earnings are found throughout the distribution but are largest below the median. Males are more affected than females, consistent with growing evidence that boys are less resilient to early environmental insults. The long-term effects seem primarily driven by changes in prenatal health rather than changes in the childhood environment.